A mentira na Grade Negativa de W. Bion - Luz, Anette Blaya (Revista de Psicanálise da SPPA, 2019)
O artigo apresenta uma breve revisão dos conceitos de Bion sobre a Grade Negativa, as transformações e os vínculos L, H e K. Busca demonstrar como esses conceitos se entrelaçam e, ao final, traz uma vinheta clínica para ilustrar na prática o que se apresentou. Palavras-chave: Transformação em alucinose; Grade Negativa; Falsidade; Mentira Abstract The lie in the Negative Grid of W. Bion The paper presents a brief review of some of Bion’s ideas concerning the Negative Grid, the transfomations and the links L, H, and K. It also tries to demonstrate how these concepts intertwine to each other. At the end a short vignette is offered to exemplify clinically what has been said. Keywords: Transformation in hallucinosis; Negative Grid; Falsehood; Lie Resumen La mentira en la Tabla Negativa de W. Bion El artículo presenta una breve revisión de los conceptos de Bion acerca de la Tabla Negativa, las transformaciones y los vínculos L, H y K. Busca demostrar cómo esos conceptos se entrelazan y, al final, trae una viñeta clínica para ilustrar en la práctica lo que se presentó. Palabras clave: Transformación en alucinosis; Tabla Negativa; Falsedad; Mentira